Thinking through television - Lembo, Ron. (Cambridge ; New York, NY : Cambridge University Press, 2000)
"This book investigates American television viewing habits as a distinct cultural form. Based on an empirical study of the day-to-day use of television by working people, it develops a unique theoretical approach integrating cultural sociology, postmodernism, and the literature of media effects to explore the ways in which people give meaning to their viewing practices. While recognising the power of television, it also emphasises the importance of the social and political factors which affect the lives of individual viewers, showing how the interaction between the two can result in a disengagement with corporately produced culture at the same time as an appropriation of the images themselves into people's lives. Accessibly written and at the cutting edge of Cultural Studies and television research, this book is essential reading for students and academics in Cultural Studies, television research, and Media and Communication Studies."--Jacket
Introduction -- Part I. Conceptions of television use: Social theory -- Social science -- Cultural studies -- Part II. Reconceptualising television use: Sociality and the problem of the subject -- Components of a viewing culture -- Part III. Documenting the viewing culture: Methodology and the turn to television -- The practice of viewing -- A typology of use -- Conclusion: the politics of television reconsidered.
Includes bibliographical references (pages 243-247) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Television broadcasting -- Social aspects -- United States; Television viewers -- United States; Télévision -- Aspect social -- États-Unis.; Téléspectateurs -- États-Unis.; SOCIAL SCIENCE -- Media Studies; Television broadcasting -- Social aspects; Television viewers; United States; Soziologie; Fernsehen; USA; Kijkgedrag; Culturele aspecten; Sociale aspecten; Electronic books; Electronic books